Association between daily sitting time and breast cancer among obese women: a nationwide population-based study - Lizhen Wang; Cuiwei Lai; Zhipeng Wu; Haoyue Luo; Tai Xu (BMC Women's Health)
Abstract Background We aimed to explore the association between daily sitting time and breast cancer in obese women, and further examine the mitigating role of physical activity in this relationship. Materials and methods A secondary analysis of cross-sectional data from the National Health and Nutrition Examination Survey (NHANES) 1999–2020 were used. Subjects were divided into four groups based on the duration of daily sitting time (< 4, 4 to 6, 6 to 8, and > 8 h). Survey-based logistic regression models, smooth curve fitting, subgroup analysis and sensitivity analysis were conducted. Results A total of 9706 obese females (mean age 50.28 years) were included in the study. Breast cancer was reported by 271 (2.8%) individuals. In the fully adjusted model, compared with those with < 4 h of daily sitting time, ORs (95%CI) for breast cancer were 1.61 (95%CI: 1.41–5.33, p = 0.001) in group with 4 to 6 h of sitting, 1.86 (95%CI: 1.35 to 4.52) in group with 6 to 8 h, and 2.21 (95%CI: 1.36–4.95, p = 0.008) with > 8 h per day. Of note, the detrimental effects of prolonged sedentary behavior on increased prevalence of breast cancer were only found in physically inactive group, but not in physically active group. Smooth curve fitting showed a positive dose-response relationship between daily sitting time and breast cancer in total participants and physically inactive group. Furthermore, obese women aged 60 years or older, non-Hispanic white, and with more than a high school education, post-menopause, and with higher obesity levels were more likely to be affected by sedentary behavior. Conclusion Prolonged daily sitting time is associated with increased prevalence of breast cancer in obese women and being physically active may mitigate this association. Prospective studies are needed to further examine this association. Clinical trial number Not applicable.